2018
DOI: 10.1124/jpet.118.250225
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Canine ATP Binding Cassette ABCB1 in Madin-Darby Canine Kidney Type II Cells Unmasks Human ABCG2-Mediated Efflux of Olaparib

Abstract: Endogenous canine ATP binding cassette B1 (cABCB1) is expressed abundantly in Madin-Darby canine kidney type II (MDCKII) cells, and its presence often complicates phenotyping of the transport process. Errors in estimating the corrected efflux ratio (cER), as a result of the variable expression of cABCB1, were examined for the dual substrates of ABCB1 and ABCG2 in MDCKII cells expressing human ABCG2 (hABCG2). cABCB1 mRNA and protein expression was 60% and 55% lower, respectively, in MDCKII cells expressing hABC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Co-incubation with quercetin increased the P app , A-to-B of prazosin ( Figure 4A) while simultaneously decreasing the P app , B-to-A ( Figure 4B) with an increasing concentration of quercetin, leading to a concentration-dependent decrease in the overall ER ( Figure 4C). Additionally, the functional expression of the efflux transporter in MDCKII/BCRP cells was also confirmed in this study, with an ER of 5.4 for prazosin (the stereotypical substrate of BCRP [27,35,36]), which decreased to 0.9 in the presence of the known inhibitor Ko143 (Figure 5C). Notably, the inhibitory effect of 10 µM quercetin on the B-to-A transport and efflux ratio was comparable to 1 µM Ko143 ( Figure 5; p > 0.05).…”
Section: Bi-directional Transport Study In Mdckii/bcrp Cellssupporting
confidence: 78%
See 3 more Smart Citations
“…Co-incubation with quercetin increased the P app , A-to-B of prazosin ( Figure 4A) while simultaneously decreasing the P app , B-to-A ( Figure 4B) with an increasing concentration of quercetin, leading to a concentration-dependent decrease in the overall ER ( Figure 4C). Additionally, the functional expression of the efflux transporter in MDCKII/BCRP cells was also confirmed in this study, with an ER of 5.4 for prazosin (the stereotypical substrate of BCRP [27,35,36]), which decreased to 0.9 in the presence of the known inhibitor Ko143 (Figure 5C). Notably, the inhibitory effect of 10 µM quercetin on the B-to-A transport and efflux ratio was comparable to 1 µM Ko143 ( Figure 5; p > 0.05).…”
Section: Bi-directional Transport Study In Mdckii/bcrp Cellssupporting
confidence: 78%
“…In addition, pharmacokinetically relevant parameters were obtained in a bi-directional transport study using MDCKII/BCRP cells, where the IC 50 values of quercetin for the inhibition of BCRP-mediated efflux were estimated to be 4.22 µM. Assuming the mechanism of inhibition to be competitive, the IC 50 value was further transformed to a Ki value of 3.91 µM, using the K m value of 128 µM [27] for prazosin. The values obtained in the bi-directional transport studies were comparable to those previously observed in MCF-7/MX and MDCKII/BCRP cells using Hoechst 33342 accumulation (IC 50 values of 7.6 and 6.9 µM, respectively) [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the presence of both P-gp-MDCK (Figure B) and BCRP-MDCK (Figure C) monolayers, dabigatran exhibited comparable or slightly greater vectorial B-A transport versus A-B transport, yielding B-A/A-B ER values of 1.8 and 2.3 for P-gp- and BCRP-MDCK cells, respectively. The efflux ratios were reduced by cyclosporine A, Ko143, and elacridar, which are dual inhibitors of P-gp and BCRP. These data indicate that dabigatran behaves as a poor P-gp and BCRP substrate in vitro. It is worth noting that the inhibitor concentrations used in this study (i.e., 10 μM for Ko143, 50 μM for elacridar, and 20 μM for cyclosporine A) are relatively high, and thus, the inhibition of endogenous canine transporters expressed in the MDCK cells might occur.…”
Section: Resultsmentioning
confidence: 86%